THE RELATIONSHIP BETWEEN STUDENTS’ VOCABULARY MASTERY AND EFL WRITING QUALITY - Zahiroh, Safrida Faradiz (RETAIN, 2021)
This quantitative study aims to find out the correlation between students’ vocabulary mastery and the writing quality of information report text. The updated version of Vocabulary Size Test and the students’ writing tasks were the instrument of this study. The researcher used an updated writing rubric to assess and give a score for the student's writing task. Fifty-four students of 9th-grade in a junior high school in Sidoarjo became the subject of this study. The data was collected by conducting a vocabulary size test and collecting the students’ writing tasks. The data analysis technique for Vocabulary Size Test was computing the students’ scores from the test. Meanwhile, the students’ writing tasks were analyzed and assessed based on the writing rubric. The Pearson correlation shows that the p-value is .562, and it is higher than the level of significance (α = .05). It does prove that there is no correlation between vocabulary mastery and writing quality in terms of scores. The coefficient correlation (r) of writing shows a negative correlation since r = -1. It concludes that vocabulary is not the only aspect to determine the writing quality. Other aspects of writing components, such as content, organization, language use, and mechanics play an essential role as well. Thus, the teachers shall teach vocabulary and other aspects of language effectively.